Load Flow Analysis Capacitor Bank dengan Metode Konpensasi Individual dan Konpensasi Global - Ruliyanta Ruliyanta; R.A. Suwodjo Kusumoputro; Idris Kusuma; Adhyarta Keraf (Jurnal Ilmiah Giga, 2022)
Abstract. Large buildings use lots of electrical equipment. The equipment includes air conditioning systems, building transportation, pumps, and others. One of the problems often encountered is the emergence of a decrease in power factor due to inductive loads. These induction machines cause this inductive load. One way to overcome this problem, Capacitor Bank is needed. The building that we observed is a building that has been operating for more than 20 years and has undergone a Single Line Diagram (SLD) change, where the capacitor bank does not work properly so the power factor is close to 0.85. This study rearranges the SLD according to the latest electrical loads in the building. The new SLD results are simulated using the Load Flow Analysis method with ETAP software, to achieve a quality factor of 0.99. In the Individual Compensation Method, it produces a savings of 13.9 kW, and this will result in a return on investment in the 40th month, and in the 2nd method, we use the Global Compensation Method which results in an improvement of 9.7 kW and a return on investment in the 57th month. Abstrak. Pada gedung-gedung besar menggunakan peralatan listrik. Peralatan tersebut seperti sistem tata udara, transportasi gedung, pompa dan lain-lain. Salah satu permasalahan yang sering dijumpai adalah timbulnya penurunan faktor daya akibat beban induktif. Beban induktif ini disebabkan oleh mesin-mesin induksi. Salah satu cara untuk mengatasinya adalah dengan menambahkan Capacitor Bank. Gedung yang kami teliti adalah gedung yang sudah beroperasi lebih dari 20 tahun dan sudah mengalami perubahan Single Line Diagram (SLD), selain itu capasitor bank tidak bekerja dengan baik sehingga faktor daya mendekati 0.85. Penelitian ini menyusun ulang SLD sesuai dengan beban listrik terbaru dalam gedung. Hasil SLD yang baru kami simulasikan dengan metode Load Flow Analysis dengan perangkat lunak ETAP, untuk mencapai faktor kualitas sebesar 0,99. Pada Individual Compensation Method menghasilkan penghematan sebesar 13.9 kW dan ini akan menghasilkan return of investment pada bulan ke-40 dan pada metode ke-2 kami pakai Global Compencsation Method yang menghasilkan perbaikan 9.7 kW dan return of investment di bulan ke-57.